Farm costs and benefits of antimicrobial use reduction on broiler farms in Dar es Salaam, Tanzania - Azabo, Rogers R.; George, Janeth I.; Mshana, Stephen E.; Matee, Mecky I.; Kimera, Sharadhuli I. (Frontiers in Antibiotics, 2022)
Of all animal derived-food, the demand for poultry meat is the most dynamic. The poultry sector can meet this demand only by introducing intensive production where antimicrobial use is inevitable. Bacterial infection prevention and control is an important factor in intensive livestock production. Antibiotics are an effective and relatively inexpensive means of preventing and controlling infections, thus maintaining animal health and productivity. The aim of this study was to gain insight into the costs and benefits of various scenarios of antimicrobial use reduction at broiler farms in Dar es Salaam, Tanzania. This study focused on the economic impact of an average broiler farm. Costs and benefits for various scenarios of antimicrobial use reduction levels were projected by a partial budget framework using the Mclnerney model. The disease cost of the current situation was US225. On reduction of antimicrobial use by 20% the avoidable disease cost was US 31, by 50% was US 83 and by 100% was US 147. A reduction in antibiotic use can only be achieved if better alternatives are available to combat disease. In conclusion, the model predicts that reducing antibiotic use increases production costs. Future studies on antimicrobial use reduction’s impact on morbidity and mortality and the efficiency of additional control and other measures of producing poultry meat without high concentrations of antibiotics are necessary.